Record of the circumstances of falls in the community: perspective in the Iberian Peninsula - Araújo, Maria de Fátima (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2018)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: to determine the diagnosis of the situation regarding documentation of falls and risk of falls in people older than 75 years in basic health units in Spain and Portugal. METHOD: mixed exploratory study in two stages: (i) quantitative descriptive of randomly selected fall records produced in one year (597 records; 197 Spanish and 400 Portuguese); and (ii) qualitative, with the purpose of knowing the perception of health professionals employing semi-structured interviews (72 professionals, 16 Spanish and 56 Portuguese). The study areas were two basic health units in southern Spain and northern Portugal. RESULTS: in the fall records, the number of women was higher. The presence of fall was associated with the variables age, presence of dementia, osteoarticular disease, previous falls and consumption of antivertiginous medication. Health professionals perceived an absence of risk assessment instruments, as well as lack of prevention programs and lack of awareness of this event. CONCLUSION: falls are perceived as an area of ​​priority attention for health professionals. Nonetheless, there is a lack of adherence to the registration of falls and risk assessment, due to organizational, logistical and motivational problems.